Injury characteristics, initial clinical status, and severe injuries associated with spinal fractures in a retrospective cohort of 506 trauma patients. Issue 3 (September 2021) - Weber, Hugues; Breton, Arnaud; Cyteval, Catherine; Millet, Ingrid; Girard, Mehdi; Lonjon, Nicolas; Capdevila, Xavier; Charbit, Jonathan
Abstract : BACKGROUND: Our aim was to describe the characteristics of vertebral fractures, the presence of associated injuries, and clinical status within the first days in a severe trauma population. METHODS: All patients with severe trauma admitted to our level 1 trauma center between January 2015 and December 2018 with a vertebral fracture were analyzed retrospectively. The fractures were determined by the AO Spine classification as stable (A0, A1, and A2 types) or unstable (A3, A4, B, and C types). Clinical status was defined as stable, intermediate, or unstable based on clinicobiological parameters and anatomic injuries. Severe extraspinal injuries and emergent procedures were studied. Three groups were compared: stable fracture, unstable fracture, and spinal cord injury (SCI) group. RESULTS: A total of 425 patients were included (mean ± SD age, 43.8 ± 19.6 years; median Injury Severity Score, 22 [interquartile range, 17–34]; 72% male); 72 (17%) in the SCI group, 116 (27%) in the unstable fracture group, and 237 (56%) in the stable fracture group; 62% (95% confidence interval [CI], 57–67%) had not a stable clinical status on admission (unstable, 30%; intermediate, 32%), regardless of the group ( p = 0.38). This decreased to 31% (95% CI, 27–35%) on day 3 and 23% (95% CI, 19–27%) on day 5, regardless of the group ( p = 0.27 and p = 0.25). Progression toward stable clinical status between D1 and D5 was 63% (95% CI, 58–68%) overall but was statistically lower in the SCI group. Severe extraspinal injuries (85% [95% CI, 82–89%]) and extraspinal emergent procedures (56% [95% CI, 52–61%]) were comparable between the three groups. Only abdominal injuries and hemostatic procedures significantly differed significantly ( p = 0.003 and p = 0.009). CONCLUSION: More than the half of the patients with severe trauma had altered initial clinical status or severe extraspinal injuries that were not compatible with safe early surgical management for the vertebral fracture. These observations were independent of the stability of the fracture or the presence of an SCI. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III.